2008
DOI: 10.1002/pon.1431
|View full text |Cite
|
Sign up to set email alerts
|

Are cancer pain and depression interdependent? A systematic review

Abstract: Pain and depression are highly prevalent in cancer patients; however, there have been no appropriately designed studies to examine a causal relationship. Although associations exist, the evidence available is not sufficient to support an interdependent relationship between pain and depression. A suitably designed longitudinal study to examine causality would be a relevant step in the research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 29 publications
5
60
1
4
Order By: Relevance
“…Data were in agreement with the literature that supported the studies which demonstrated the relationship between pain and depression [28]. Besides our study showed that the relationship between depression and the affective dimension of pain, was mediated by negative cognitive appraisal of pain, whereas the impact of sensory dimension of pain on depression is mediated by a focus on somatic symptoms [29]. The finding of high levels of pain sensation/intensity might emphasize cancer pain variability over time with the severity of the disease, while the finding of high affect might be related to a perception of their pain as health or life threatening.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Data were in agreement with the literature that supported the studies which demonstrated the relationship between pain and depression [28]. Besides our study showed that the relationship between depression and the affective dimension of pain, was mediated by negative cognitive appraisal of pain, whereas the impact of sensory dimension of pain on depression is mediated by a focus on somatic symptoms [29]. The finding of high levels of pain sensation/intensity might emphasize cancer pain variability over time with the severity of the disease, while the finding of high affect might be related to a perception of their pain as health or life threatening.…”
Section: Discussionsupporting
confidence: 82%
“…Mood disorders are more prevalent in oncological patients with pain than those without pain. Our data confirmed data of literature concerning the relationship between the presence of depression and pain [29]. Our study had some limitations.…”
Section: Discussionsupporting
confidence: 81%
“…La depresión es un trastorno del afecto caracterizado por estados de ánimo de abatimiento y tristeza; afectando el cumplimiento terapéutico, habilidades de auto-cuidado, deterioro de la calidad de vida y mayor sintomatología (35,36) . La prevalencia de depresión durante el tratamiento en pacientes con CT reportan entre 14,6 a 27% (6,8,33) .…”
Section: Depresiónunclassified
“…Gauthier et al 10 reported an association between pain acceptance and psychological well-being in patients with advanced cancer, but no association with pain or physical function. This finding has important implications, especially given that cancer patients frequently experience co-morbid pain and depression, 2 two factors that react to one another and share common biological pathways. 11 The neurotransmitter imbalance occurring in depression is associated with greater sensitivity to pain and changes in pain perception.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Pain acceptance could help cancer patients adapt to pain, since it has proven valuable in determining physical and emotional adjustment to chronic non-malignant pain.vPain acceptance refers to the continuation of activities despite experiencing pain, as well as the willingness to accept the presence of pain in order to discontinue futile attempts to control it and live a satisfying life. 4 Acceptance has been associated with improved emotional, physical and social functioning in chronic pain sufferers.…”
Section: Introductionmentioning
confidence: 99%